The Boolean closure of DR-recognizable tree languages - Jurvanen Eija (Acta cybernetica, 1992)
The family DRec of tree languages recognized by deterministic root-tofrontier (top-down) tree automata is not closed under unions or complements. Hence, it is not a variety of tree languages in the sense of Steinby. However, we show that the Boolean closure of DRec is a variety which is properly included in the variety Rec of all recognizable tree languages. This Boolean closure is also compared with some other tree language varieties.